Medical and surgical management of moderate-to-severe inflamatory bowel disease - Paredes Méndez, Juan Eloy (2021)
The management of inflammatory bowel disease (IBD) is mainly medical, however, more than 70% of patients with Crohn's disease (CD) and 25% with ulcerative colitis (UC) will require surgery during their lifetime. Objective: To evaluate medical, surgical management and evolution in patients with moderate-to-severe IBD. Materials and methods: Observational, descriptive, retrospective study from January 2011 to December 2019 in the Gastroenterology Service of the Guillermo Almenara Irigoyen National Hospital, Lima-Peru. Results: Twenty two patients with IBD, 17 with CD and 5 with UC were included. Male predominance (59%). Emergency surgery was performed in 35.2% and 60% of patients with CD and UC, respectively. Stenosis and toxic megacolon were the most frequent indications. According to the type of surgery, hemicolectomy (41%) and intestinal resection (41%) were the most frequently performed in CD, while in UC it was total colectomy (60%). Among the postoperative complications, dehiscence/fistula and intra-abdominal collections were the most frequently reported in CD; whereas in UC it was surgical site infection and adynamic ileus. After surgery, biologics and 5-ASA associated with immunomodulator were the most used treatment in CD and UC, respectively. Mortality was 17.6% in CD and 60% in UC. Conclusions: Surgical treatment is an option in the management of moderate-to-severe IBD. Emergency surgery in IBD continues to have a high morbidity and mortality rate.